THE RELATIONSHIP BETWEEN COMMON MANAGEMENT AND ECOTOURISM REGULATION: TRAGEDY OR TRIUMPH OF THE COMMONS? A LAW AND ECONOMICS ANSWER - SAMÀ, Danilo (Journal of Advanced Research in Law and Economics; Vol 2 No 1 (2011): JARLE Volume 1 Issue 1(3) Summer 2011, 2017)
Since its origin, ecotourism development has been at the centre of controversial and heated debates within the environmental and scientific society. On one hand, it has been considered as a model of responsible and sustainable tourism with the capacity to guarantee the conservation of the current biodiversity level and cultural identity, to educate the tourists about preservation and to improve the economic activity and the standard of living of the populations affected. On the other hand, it has been criticized for actually being a mere instrument in the hands of capitalist and western firms to commercially exploit the natural resources available in the less developed countries. Thus, are the ecotourism projects more likely to be profitable and successful in territories where the common resources are controlled by the state or managed by private firms? Considered the most frequent and spontaneous solution noticed in the ordinary daily life of the emerging countries, meaning natural resources owned communally by local institutions, does ecotourism impede or reinforce this management function of coordinating and controlling? The empirical researches conducted in literature tried to answer to some of the above-mentioned questions and offered the opportunity for a Law and Economics assessment of the problem related to the common-pool resources.
Keywords: Common-Pool Resources, Commons Management, development, ecology, environment, governance, property rights, regulation, sustainability, tragedy of the Commons